Editorial [Optica Applicata, Vol. 35, 2005, nr 3] - Tłaczała, Marek (Oficyna Wydawnicza Politechniki Wrocławskiej, 2005)
We have great pleasure in presenting the new edition of Optica Applicata, which gives account of some latest achievements of a number of research centres in Poland. The papers are an obvious evidence of significant growth of interest in the technological development of fabrication of advanced test and device structures and progress in methods used to characterize semiconductor structures, metals, dielectrics and thin films. The advancement of investigation into the structures and devices taking advantage of the quantum effects deserves special attention. We would like to emphasize the fact that much work was done in co-operation with recognized research centres from different countries. For the sake of convenience this issue has been divided into three parts: surface physics, thin film structures and modern semiconductor and other materials.
Optica Applicata, Vol. 35, 2005, nr 3, s. 321-322
Keywords: optyka; editorial